(untitled) (Journal of human and social sciences, 2026)
This study reviews the book “The Fertility Reference in Libyan Demographic Data” by Dr. Mohamed Mohamed Misbah Al-Sharif, which addresses demographic phenomena in Libya, with particular focus on fertility and its relation to human development and population dynamics. The book analyzes demographic indicators, fertility measures, and the influence of social, economic, and cultural factors, while highlighting the risks of demographic shifts that may lead to future crises. It stresses the importance of demographic data in diagnosing population realities and formulating national population policies.